Pengaruh Daya Tarik Wisatawan, Muslim Friendly Tourism, Dan Media Sosial Berbasis Konten Terhadap Keputusan Berkunjung Di Wisata Religi Gunungpring Muntilan - Pramudita, Desti Ayu; Nurhadi, Bayu (CV ODIS, 2025)
This study aims to determine the influence of tourist attractions, Muslim Friendly Tourism, and Content-Based Social Media on the decision to visit Gunungpring Muntilan Religious Tourism. This study uses quantitative methods with primary data types and purposive sampling as sampling techniques. This research was conducted by distributing questionnaires directly to respondents in the form of a written list of questions with a sample of 385 respondents. The test was carried out using data instrument tests, classical assumption tests, multiple linear regressions, and hypothesis tests. The analysis tool uses Eviews 13. Based on the results of data analysis in the T test, it shows that tourist attraction (X1) has a positive and significant effect on the decision to visit (Y). Muslim friendly tourism (X2) has a positive and significant effect on the decision to visit (Y). Content-based social media (X3) has a positive and significant effect on the decision to visit (Y).